Pengaruh Wisata Edukasi dan Keindahan Arsitektur Terhadap Keputusan Bekunjung ke Museum Bank Indonesia - Sulaeman, Muhammad Bilal; Pangkerego, Eduard Rudolf; Maulana, Alifatqul (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2111, 2026)
Museums serve not only as institutions for preserving history and culture but also increasingly as tourism destinations that offer educational and aesthetic experiences. This study aims to analyze the influence of educational tourism and architectural beauty on visitors’ decisions to visit the Bank Indonesia Museum. A quantitative approach with an explanatory research design was employed. Primary data were collected through a five-point Likert-scale questionnaire administered to 100 respondents selected using purposive sampling. The respondents were visitors aged 17 years and above who had visited the Bank Indonesia Museum. The data were analyzed using linear regression analysis. The results show that educational tourism has a positive and significant effect on the decision to visit, with a regression coefficient of 0.450 and a significance level of 0.000. Architectural beauty also has a positive and significant effect, with a regression coefficient of 0.380 and a significance level of 0.000. Simultaneously, both variables significantly affect the decision to visit, with an F-value of 62.430 and a significance level of 0.000. These findings highlight the importance of integrating educational functions and architectural appeal in developing the Bank Indonesia Museum as a cultural and educational tourism destination. Keywords: educational tourism, architectural beauty, visit decision, museum